Análise fenotípica e molecular da produção de biofilmes por estirpes de staphylococcus aureus isoladas de casos de mastite subclínica bovina - Melo, Poliana de Castro [UNESP]; Ferreira, Luciano Menezes; Nader-Filho, Antonio [UNESP]; Zafalon, Luiz Francisco; Godoy Vicente, Hinig Isa (Universidade Federal de Uberlândia (UFU), 2012)
Biofilm formation is considered an advantage for Staphylococcus aureus mastitis isolates, facilitating bacterial persistence in the udder. It requires attachment to mammary epithelium, proliferation and accumulation of cells in multilayers and enclosing in a polymeric matrix known as exopolysaccharide. The objective of this study was to evaluate the ability of Staphylococcus aureus isolated from bovine subclinical mastitis for formation of biofilms. A total of 94 Staphylococcus aureus strains obtained from milk samples of cows suffering from subclinical mastitis in dairy herds on two properties in the state of São Paulo were evaluated. These strains were characterized by in vitro biofilm formation, and by the presence of icaA and icaD genes which are responsible for intercellular adhesion. The results revealed that 98.9% of the isolates produced biofilm in vitro by adherence in sterile 96-well "U" bottom polystyrene tissue culture plates; 95.7% of the isolates possessed the icaA and icaD genes. These bacterial isolates biofilm producers may impair eradication of chronic mastitis, rendering antibiotherapy less effective. The detection of biofilm forming ability in mastitis isolates may provide useful information for more adequate therapeutic regimen and for preventive actions in the control of those bacterial isolates in bovine herds.

A formação de biofilmes é considerada uma vantagem que alguns Staphylococcus aureus isolados de mastite bovina possuem, facilitando a permanência dos mesmos no úbere. Isto requer a adesão das bactérias no epitélio mamário com proliferação e formação de multicamadas de células envolvidas por uma matriz polimérica conhecida como exopolissacarídeo. O objetivo deste estudo foi avaliar a produção de biofilmes das estirpes de S. aureus isoladas de casos mastite subclínica bovina. Estudou-se 94 estirpes de S. aureus obtidas do leite de vacas com mastite subclínica oriundas de duas propriedades rurais no estado de São Paulo. Essas estirpes foram caracterizadas quanto a produção de biofilmes pelos testes de aderência em microplacas e pela presença dos genes icaA e icaD responsáveis pela produção do polissacarídeo de adesão intercelular. Os resultados obtidos revelaram que no teste de aderência em placas, 98,9% das estirpes produziram biofilme e a presença dos genes icaA e icaD foi encontrada em 95,7% das estirpes de S. aureus. Bactérias produtoras de biofilmes no epitélio mamário diminuem a efetividade dos antimicrobianos, por isso a detecção de S. aureus produtoras de biofilmes têm importância no entendimento da patogenia desse agente, além de permitir uma melhor adoção de medidas de prevenção e controle.
Phenotypic and molecular analysis of biofilm production by staphylococcus aureus strains isolated of bovine mastitis case
Keywords: Biofilms; Bovine mastitis; icaA, icaD genes; Staphylococcus aureus